Histone Deacetylase 6-Selective Inhibitors and the Influence of Capping Groups on Hydroxamate-Zinc Denticity - Porter, Nicholas J. (J Med Chem, 2018)
Four crystal structures are presented of Histone Deacetylase 6 (HDAC6) complexes with para-substituted phenylhydroxamate inhibitors, including bulky peptoids. These structures provide insight regarding the design of capping groups that confer selectivity for binding to HDAC6, specifically with regard to interactions in a pocket formed by the L1 loop. Capping group interactions may also influence hydroxamate-Zn2+ coordination with monodentate or bidentate geometry.